Analisis Dampak Kenakalan Remaja Terhadap Prestasi Belajar Siswa di SMP Muhammadiyah 57 Medan - Kaila Wanda; Rizka Harfiani (Jurnal Cakrawala Akademika, 2024)
This research discusses the analysis of the juvunile delinquency on student learning achievement at SMP Muhammadiya 57 Medan. The aim of this research is to analyze whether there is an impact of juvenile delinquency on children’s learning achievement, factors that can influence juvenile delinquency. This research uses qualitative descriptive methods, data collection techniques and by means of observation, interviews and documentation. Juvenile delinquancy has a negative impact on student learning achievement at SMP Muhammadiyah 57 Medan. This implication of this research can be used to develop intervention programs aimed at reducing levels of juvenile delinquency and increasting the learning achievement of adolescent students.